"I think it is important to speak multiple languages theoretically in order to communicate to different types of people" - Elissa Braunstein; Yannis Dafermos; Torsten Niechoj (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
"The interview was conducted by Yannis Dafermos and Torsten Niechoj on 21 October 2022 in Berlin during the 26 th Conference of the Forum for Macroeconomics and Macroeconomic Policies (FMM) on Post-Keynesian Economics and Global Challenges.
Keywords: 330